Gadis Antariksa Icon: Fostering Environmental Awareness through Mangrove Ecosystem Education - Whisnuwardani, Indri Rosemaya; Noriko, Nita; Nurhasanah, Nunung (Universitas Negeri Semarang, 2025)
Innovation in mangrove ecosystem education is crutial for enganging younger generations in global climate change mitigation efforts. This study employs a qualitative approach to develop a Knowledge Capture (KC) model using Soft System Methodology (SSM), profiding a framework aligne with knowledge objectives: normative, operational, strategic and interactive planning. The CATWOE analysis (Customers, Actors, Transformation, Worldview, Owners, Environment) is applied to understand complex interactions within social and organizational systems, ensuring all stakeholder perspectives are considered. The learning innpvation is structures through eight stages: Focus Group Discussion with educators, environmental observation, knowledge management via applied science seminars, evaluation and development of climate change activities, collaboraive development, cross-subject collaboration, development of a Phase E Biology teaching module, and establisment of a science greenhouse for education. These resuls demonstarate that he Knowledge Capture process using the SSM approach effectively advances mangrove ecosystem education as a cliamte change mitigation strategy. Quantitative validation employed questionnaires analyzed with a Likert scale to assess participants' knowledge and attitudes, confirming high instrument validity and reliability. These findings affirm the potential of hte Gadis Antariksa Icon, fostering environmental awarness through mangrove ecosystem education.